Evolution of the soot particle size distribution along the centreline of an n-heptane/toluene co-flow diffusion flame - Dreyer, Jochen A. H. (2021)
A newly developed experimental set-up for studying liquid hydrocarbon combustion in the well-established Yale burner was used to investigate the correlation between fuel composition and its sooting propensity. Soot particle size distributions (PSDs) and flame temperatures along the centreline of an n-heptane/toluene co-flow diffusion flame are reported. The results are compared to soot temperature and volume fraction profiles obtained using colour ratio pyrometry. The addition of toluene (0, 5, 10, and 15 mol%) to heptane moved soot inception to lower heights above the burner (HAB). The earlier inception extended the soot growth zone in the toluene-laden flames, leading to larger soot primary and agglomerate particles. Toluene addition had little influence on the maximum soot number density, indicating that the observed increase in soot volume fraction can mainly be attributed to the increase in particle size. The reported PSDs inside a vapour-fed diffusion flame are the first of their kind and provide a comprehensive dataset for future studies of combustion chemistry and soot particle models.